RELASI SOSIAL VIRTUAL SEBAGAI RUANG KOMUNIKASI POLITIK - Endang Dwi Sulistyoningsih (JUSS (Jurnal Sosial Soedirman), 2018)
Victory is the primary goal for eligible participants in legislative, regent, governor, and presidential elections. The use of social media became a means of garnering support from the public, but on the other hand openly getting attacks from supporters of the opposing camp. Mutual news "hoax" that spread on social media is a problem that has not been resolved until now. Social media becomes a force as well as a threat because it is transformed into a digital world that does not recognize the boundaries of state sovereignty as well as the political and social structure of society. Students are members of the community of social media users who are critical of the development of virtual social relationships that are transformed into a space of political communication. This study used qualitative research methods. The purpose of this study is to analyze the meaning of students of social media users and analyze social media influence on the political participation of its users. Social media has the following meanings; First, social media is interpreted as a form of public opinion. Second, social media as the most democratic media. Third, social media as a driver of change. Fourth, social media as a two-way communication media. Fifth, social media as an opponent's surveillance tool. The implication of this research is expected to be more critical, hopefully, the political communicator is more professional and wise in conveying their political message. The goal of winning or just the opposite is that society becomes less sympathetic, and undermines the self-image of political participants.